IMPLEMENTASI MODEL PEMBELAJARAN GUIDED DISCOVERY BERBASIS MULTIMEDIA INTERAKTIF UNTUK PEMAHAMAN MATA KULIAH PEMBINAAN KOMPETENSI MENGAJAR - Irwanto (Bajang Institute, 2021)
The background of the research is the lack of understanding of students in teaching competency development courses. Especially in understanding teaching practice which consists of three parts, namely teaching practice not using learning media, practice using learning media, and teaching practice. In an effort to understand students, it can be done through the implementation of guided discovery models based on interactive multimedia. The purpose of this study was to determine the implementation of interactive multimedia-based guided discovery model on teaching competence, which consists of three skills. The research method used is an experimental method with a one group pretest-posttest design. Respondents in this study were students of the electrical engineering vocational education study program, semester six of the 2020/2021 academic year at Sultan Ageng Tirtayasa University. The results showed that the pretest results obtained the average value of the experimental class of 52.12 for the upper group, 43.32 for the middle group and 61.31 for the lower group, while the posttest results obtained an average value of 89.31 for the upper group, 80.76 for the upper group. middle and lower group 79.32. The student response to the implementation of guided discovery learning model assisted by interactive multimedia was 89% included in the very good category, so it can be said that the guided discovery learning model assisted by interactive multimedia could improve students' understanding in teaching competency development courses.